Constitution of the State of Washington, art. 1, § 24 (August 22, 1889). - (:unkn) unknown (My University, 1889)
The right of the individual citizen to bear arms in defense of himself, or the State, shall not be impaired, but nothing in this section shall be construed as authorizing individuals or corporations to organize, maintain or employ an armed body of men."
Keywords: GUARANTEED RIGHT